MODERN UKRAINIAN PHOTO BOOK AS AN OBJECT OF CONCEPTUAL ART OF POSTMODERNISM - Safronova, A. V. (Art and Design, 2021)
Purpose. The purpose of the study is to identify the features of modern Ukrainian photo books, which have become a striking example of following the trends of postmodern art. Methodology. The study is based on the integrated use of historical, comparative methods, systems analysis, synthesis, generalization. Results. The modern Ukrainian photo book is considered as a work of conceptual art of postmodernism. Certain artistic and compositional features and design techniques of Ukranian photobooks are identified; originality of form; author's presentation of textual, content and visual components of the indoor unit: inclusion of ready-made images (ready-made) and photo manipulation, use of collages, photos of utilitarian objects, etc. Scientific novelty. On the example of art history analysis of a number of well-known Ukrainian photobooks, the characteristic features of the photobook as an object of modern conceptual art is determined, the features of figurative, stylistic, artistic and compositional design solutions are systematized. Practical significance. The artistic and compositional features and design techniques used by photographers in the implementation of creative ideas have been identified, the theoretical basis of modern conceptual art have been expanded that can be useful in future creative projects of photobooks that will have both artistic and commercial value.